Information unreliability minus nuclear safety: how «fake news» and «hiding shil in the bag» brings the world more closer to another nuclear disaster - Evgeny V. Ugrinovich; Dmitry V. Mun; Vladislav V. Popeta (Informaciâ i Innovacii, 2018)
In the article the authors put forward the thesis about the need for the immediate organization of a multilevel, international counteraction to the production and dissemination of false information, both through traditional media and through social networks. As an example, the authors cites an effect of fake news, which, together with untimely and incomplete informing of the public, put the negative impact on the further development of the world nuclear energy.